An Improved Route to Purin-6-yl Magnesium Halides by Metal–Halogen Exchange in Dichloromethane - Gordon, Malcolm R.; Lindell, Stephen D.; Richards, Daniel (Synlett, 2018)
Treatment of a solution of 9-benzyl or 9-phenyl 6-iodopurine in dichloromethane with an ethereal solution of ethylmagnesium bromide at ambient temperature generates the corresponding purin-6-yl magnesium halides which react with aldehydes to give carbinols in 55–80% yield. Performing the same procedure with THF as solvent gave carbinols in much lower yields (≤15%).
Keywords: nucleobases; purin-6-yl magnesium halides; Grignard; dichloromethane; carbinols